Reconstruction of road construction in Kazakhstan problem analysis - Kasym Қасым (Рroblems of engineering and professional education, 2023)
In May 2012, the issue of the reconstruction of the road sector in the modernization of the economy of the Republic of Kazakhstan in the past, adopted at a meeting of the State Commission. As part of the task of the state of international and national significance for public roads construction, reconstruction and maintenance work in progress, quality control; as well as the implementation of the collection of the levy of toll highways.